Factors influencing halal cosmetics purchase behaviour of working adults and university students in Malaysia - Adlin Masood, (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2021)
Halal cosmetics sector is fast expanding in lieu of the growing affluent 1.8 billion Muslim population globally. Unlike attention given to research on consumer purchase behaviour of halal food, consumer purchase behaviour of halal cosmetics is limited. To date, out of forty-five research papers on halal cosmetics, only four research papers have been conducted to deliberate on halal cosmetics consumer purchase behaviour. To discover the current state of knowledge and practice on halal consumer behaviour, a review of published literature in hightiered bibliographic data base was conducted. This was followed by affirmation from a personalised online survey on Malaysian consumers. Consequently, the study identified prevailing factors affecting halal cosmetics consumer purchase behaviour of working adults and students in Malaysia and unearthed peculiarities in their purchase behaviour. In tandem the study also noted the knowledge gaps for future research. Results from the study will assist halal cosmetics companies to design marketing programs that can maintain and grow their customer base both domestically and internationally. Recommendations was also made on how to create strategic marketing programs leveraging on IR4.0 technology.